Dealing with welfare conditionality : implementation and effects / edited by Peter Dwyer. - Dwyer, Peter (Peter James) (Welfare conditionality., 2019)
This edited collection considers how conditional welfare policies and services are implemented and experienced by a diverse range of welfare service users across a range of UK policy domains including social security, homelessness, migration and criminal justice.